Chemical engineering of mixed halide hexaborates as nonlinear optical materials. Issue 109 (11th November 2016) - Xia, Mingjun; Hou, Zhanyu; Yang, Yi; Xu, Bo; Liu, Lijuan; Wang, Xiaoyang; Lin, Zheshuai; Li, R. K.; Chen, Chuangtian
Abstract : Mixed polar halide hexaborates were investigated to unravel their microscopic structural variations and the compositional impacts on optical properties. Abstract : Mixed nonlinear optical (NLO) crystals have been widely investigated to precisely optimize their optical properties by controlling the compositions, and have drawn immense attention in the laser science and technology field. Herein, a series of mixed NLO crystals K3 B6 O10 Br1− x Cl x ( x = 0, 0.21, 0.35, 0.47, 0.57, 0.75 and 1) were obtained using spontaneous nucleation and a bulk crystal of K3 B6 O10 Br0.53 Cl0.47 with the size 41 × 26 × 15 mm 3 was successfully grown by a top seeded solution growth (TSSG) method. The NLO properties of the mixed crystals were studied by combination of second harmonic generation (SHG) tests and first-principles calculations. As a potential mixed crystal for practical application, the optical properties of the K3 B6 O10 Br0.53 Cl0.47 crystal including transparency range, refractive indices, the shortest SHG phase-matching wavelength and angle were investigated. The results indicate that the optical performance of the mixed crystals can be effectively adjusted to optimize practical high power laser output by tuning substitution compositions.